2017
DOI: 10.1016/j.techfore.2017.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Clashing institutional interests in skills between government and industry: An analysis of demand for technical and soft skills of graduates in the UK

Abstract: Technological knowledge and skills provide a basis for developing national competitiveness. However, there is an emerging clash of interests in the UK labour market between employers and policy makers. The former requests highly skilled workers who often jealously train in house for their specific operations while the latter aims to reduce unemployment through the expansion of vocational training to lower skilled workers. Universities need to find their strategic position in the knowledge economy characterised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 67 publications
0
57
0
1
Order By: Relevance
“…This demand for new skills compels universities to improve their education plans, and also encourages organizations to develop training plans for workers [196]. However, difficulties in training the workforce are evident both in universities due to gaps in teaching [197], and in organizations due to the lack of interest of employees due to training programs that often do not meet the real needs of employees due to the lack of sense of belonging and purpose, as well as for the failure of communication between the company and employees [196]. Therefore, there are challenges both in the sphere of education for the development of I4.0 workforce skills as well as in human resources challenges to support manage and develop such skills [198,199].…”
Section: G Industry 40 and Social Sustainabilitymentioning
confidence: 99%
“…This demand for new skills compels universities to improve their education plans, and also encourages organizations to develop training plans for workers [196]. However, difficulties in training the workforce are evident both in universities due to gaps in teaching [197], and in organizations due to the lack of interest of employees due to training programs that often do not meet the real needs of employees due to the lack of sense of belonging and purpose, as well as for the failure of communication between the company and employees [196]. Therefore, there are challenges both in the sphere of education for the development of I4.0 workforce skills as well as in human resources challenges to support manage and develop such skills [198,199].…”
Section: G Industry 40 and Social Sustainabilitymentioning
confidence: 99%
“…Hence, the need for critical and reflective thinking, problem-solving abilities, selfmanagement, learning, and related competencies is continually increasing across all disciplines (Makkonen, 2017). Several prior studies have indicated that in addition to the influence of basic education on employability, factors like personal conditions, interpersonal relations, and external factors that cannot be acquired in higher education should also be considered (Ahmed et al, 2015;Cacciolatti et al, 2017;Blázquez et al, 2018). Hennemann and Liefner (2010), who developed a graduate employability training process, summed up a comprehensive structure of impact factors to explain the capacity, capability, and competence (Blázquez et al, 2018) that are important elements in the process of developing employability (Lurie and Garrett, 2017;Likisa, 2018).…”
Section: Student Employabilitymentioning
confidence: 99%
“…Hence, the need for critical and reflective thinking, problem-solving abilities, self-management, learning, and related competencies is continually increasing across all disciplines ( Makkonen, 2017 ). Several prior studies have indicated that in addition to the influence of basic education on employability, factors like personal conditions, interpersonal relations, and external factors that cannot be acquired in higher education should also be considered ( Ahmed et al, 2015 ; Cacciolatti et al, 2017 ; Blázquez et al, 2018 ).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…As universities have become more accessible, the number of graduates has increased, with knock-on effects on the graduate job market in terms of competition (Beaumont, Gedye & Richardson, 2016;Tomlinson, 2012). Previously, employers would simply seek those who had obtained a good degree, but now graduates are expected to offer more and demonstrate well-developed transferable skills (Cacciolatti, Lee & Molinero, 2017;Saunders & Zuzel, 2010;Tymon, 2013), especially in the UK labour market, where sociocultural qualifications are most highly prized (Manninen & Hobrough, 2000). Thus, graduates who lack soft skills are at a great disadvantage in an overcrowded and highly competitive market (Tymon, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Universities are under increased pressure to produce an abundance of well-educated and well-rounded graduates who are fully prepared for entering their chosen career upon completion of their studies (Tomlinson 2012;Tymon 2013), with both the government and employers fully expecting institutions to offer programmes which embed all the necessary technical and soft skills that are required (Yorke & Knight, 2006;Cacciolatti, Lee & Molinero, 2017;Gazzard, 2011). The use of league tables which rank universities on different indicators, including graduate prospects (McMurray, et al, 2016), influence the quantity and quality of students who apply to study and the funding awarded to the university (Gibbons, Neumayer & Perkins, 2015).…”
Section: Introductionmentioning
confidence: 99%